2011
DOI: 10.1177/0887302x11414874
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Sustainable Apparel Design Challenges With Problem-Based Learning

Abstract: As consumers' social and environmental concerns have grown in the last decade, so has interest in eco-fashion. Behind fast-changing fashion trends, the apparel industry generates substantial environmental and resource depletion problems throughout the textile lifecycle. To respond to these trends, fashion designers and merchandisers have been motivated to practice sustainability in design and production. Some sustainable options are available, such as organic fibers and environmentally safe dyes. Still, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 23 publications
5
87
0
2
Order By: Relevance
“…Furthermore, textile companies' supply chains are not only globally dispersed [42] and characterized by a strong social and environmental impact [43], but are also linked to a significant number of sustainability issues related to suppliers [44]. As a result, market participants in the textile sector are increasingly under the spotlight for their involvement in social and environmental issues [45].…”
Section: Sustainable Supply Chain Management In the Textile Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, textile companies' supply chains are not only globally dispersed [42] and characterized by a strong social and environmental impact [43], but are also linked to a significant number of sustainability issues related to suppliers [44]. As a result, market participants in the textile sector are increasingly under the spotlight for their involvement in social and environmental issues [45].…”
Section: Sustainable Supply Chain Management In the Textile Sectormentioning
confidence: 99%
“…Paradoxically, customers pressure textile companies with their consumption behavior by demanding variety and affordability of products. At the same time, a growing awareness for sustainability arises [43] Moreover, sustainability issues in textile supply chains increasingly attract the concern of other stakeholders, including NGOs, local governments and the media, creating additional pressure to address sustainability issues [49].…”
Section: Sustainable Supply Chain Management In the Textile Sectormentioning
confidence: 99%
“…Despite the importance of achieving a sustainability approach as a whole, some academic literature discusses either environmental or social sustainability perspectives without considering them simultaneously (Carter and Liane Easton 2011;Ashby, Leat, and Hudson-Smith 2012). Instead, adopting a sustainability approach that identifies the synergies between these two aspects is becoming compulsory for SCM, in particular, within the fashion industry, where many companies are currently implementing different activities to lower their impacts on the environment and society (Chen and Burns 2006;Allwood et al 2008;Gam and Banning 2011;Niinimäki and Hassi 2011;Armstrong et al 2015). As suggested by Kozlowski, Bardecki, and Searcy (2012), social and environmental aspects within fashion supply chains should not be treated separately, but rather simultaneously, as they intertwine and influence each other.…”
Section: Drivers and Barriersmentioning
confidence: 99%
“…Contrarily, Shen et al found preventing sweatshop labor is more important to consumers than protecting the environment, despite the fact that they had little knowledge on the sweatshop situation (Shen et al, 2012). This demonstrates, on the one hand, limited knowledge and misconception of consumers regarding sustainability, since they define it simply without describing it in detail or with examples (Carew & Mitchell, 2002;Gam & Banning, 2011). On the other hand, consumers' perception of importance for certain sustainable issues differs with regard to the respondent sampling group.…”
Section: Customer Perception Of Sustainable Fashionmentioning
confidence: 99%